Determinan Ekspor UMKM Binaan Kantor Perwakilan Bank Indonesia Provinsi Bali - Laksono, Dwi; Setyari, Ni Putu Wiwin (Jurnal Ilmiah Wahana Pendidikan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia are one of the largest informal sectors that absorb a significant amount of the workforce, and it is hoped that they can contribute to the growth of the export market. Bank Indonesia, as the Central Bank, continues to make efforts to provide the best contribution in order to enhance the role of MSMEs in the economy. This research aims to determine the relationship between product innovation, demand, social capital, product innovation, and culture with the export potential of MSMEs under the supervision of the Bank Indonesia Representative Office in Bali Province. The sample size in this research consists of 53 supervised MSMEs, divided into two categories: export and non-export MSMEs. The sampling technique used in this research is saturation sampling. Data collection was conducted through interviews, non-participant observation, and in-depth interviews. Orange data mining was used as the data analysis method in this research. The results of the research indicate that innovation, culture, and e-commerce have a very weak correlation with export potential, while social capital and demand have a strong correlation with the export potential of MSMEs under the supervision of the Bank Indonesia Representative Office in Bali Province